IDENTIFIKASI MATERI YANG DIANGGAP SULIT UNTUK PELAJARAN MATEMATIKA PADA JENJANG SMP KELAS 8 - Leonard Leonard; Huri Suhendri; Hasbullah Hasbullah; Amanda Mevianti; Novita Cahyo Puteri (LPPM Universitas Bina Bangsa, 2022)
This study aims to identify mathematical material that is considered difficult at the Junior High School level class VIII. This research used a descriptive method with interview techniques. Needs analysis was carried out to experts, namely senior teachers in 4 cities in Indonesia, namely Pekanbaru, Jakarta, Cirebon, and Yogyakarta. Based on the results of the needs analysis, it was found that there are at least three materials that are difficult for students to master, namely straight-line equations, building flat-side spaces, and opportunities. This is expected to provide inspiration and further research opportunities, namely research aimed at the development of learning tools, including learning methods, learning media, and learning evaluation tools, so that materials that are considered difficult can be resolved immediately and students can master them well